Plant diversity increases the abundance and diversity of soil fauna: A meta-analysis - Zhang, Yakun; Peng, Sai; Chen, Xinli; Chen, Han Y.H. (Geoderma, 2022)
•Meta-analysis up to 2021 on the effect of plant diversity on soil fauna.•Positive mixture effects were found on fauna diversity on average.•The mixture effects on fauna increased with plant species richness in mixtures.•The mixture effects on fauna abundance increased over time in diverse mixtures. Soil fauna communities are an important component of soil biodiversity, which is key to myriad terrestrial ecosystem processes. However, despite the current alarming loss of plant diversity, it remains unclear how plant diversity affects soil fauna communities. By synthesizing 623 paired observations of plant mixtures and corresponding monocultures from 40 studies, we examined the effects of plant mixtures on soil fauna abundance and diversity. Further, we investigated the dependence of mixture effects on species richness, stand age, climate conditions, and ecosystem types. We found that, on average, the diversity of soil fauna was 10% higher in plant mixtures than the average of corresponding monocultures, while the abundance of fauna did not differ significantly between the mixtures and the average of monocultures. The mixture effects on both soil fauna abundance and diversity increased with plant species richness in mixtures, which resulted in higher abundance and diversity of soil fauna in species-rich plant mixtures than the averages of their corresponding monocultures. Moreover, the effects of plant mixtures on soil fauna abundance increased over time in diverse species mixtures. After accounting for the effects of species richness in mixtures and stand age, the effects of plant mixtures on the abundance and diversity of soil fauna were consistent across soil depths, ecosystem types, and climate conditions. Our analysis highlights the potential importance of plant diversity conservation for the maintenance of soil fauna communities.